Strategi Pemasaran Usaha Makanan Khas Batak Karo Kamikaze di Kota Manado - Gurusinga, Louis Stevania Br; Mandei, Juliana Ruth; Maweikere, Audrey Julia Maria (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
This study aims to identify and evaluate the marketing strategies applied by the Kamikaze Batak Karo Traditional Restaurant in Manado City, an ethnic culinary business that introduces Batak Karo cuisine outside its cultural origin. The research employed a descriptive quantitative method with the 7P marketing mix framework, comprising product, price, place, promotion, people, process, and physical evidence. Data were collected from 39 respondents through closed-ended questionnaires and interviews with the business owner, analyzed using a three-point Likert scale. Findings indicate that all marketing aspects were rated “good” by consumers, except for pricing, which was considered “fair” due to the lack of direct-purchase discounts. The physical evidence aspect received the highest score, highlighting the role of visual appeal and ethnic ambiance in shaping a positive business image. With an average marketing score of 102 out of a maximum of 117, the marketing strategy of Rumah Makan Kamikaze is categorized as effective. These results affirm that culturally-based differentiation, when aligned with adaptive marketing strategies, can successfully engage cross-cultural consumers in the local agribusiness market.